Strategi keuangan berbasis syariah dalam meningkatkan kinerja dan efisiensi operasional usaha mikro, kecil, dan menengah (umkm) di era digital - Puspita, Ririnn Diyah (Maliki Interdisciplinary Journal, 2025)
This study examines the application of sharia-based financial strategies in improving the performance and operational efficiency of Micro, Small and Medium Enterprises (MSMEs) in the digital era. Economic digitalization has driven significant changes in the way MSMEs access financial services, but many businesses still experience obstacles in utilizing conventional banking services. Islamic banking products, such as Mudharabah, Musyarakah, and Murabahah, which are integrated with digital technology, offer more transparent and fair financing solutions. Through a descriptive qualitative approach, this study explores the role of digital Islamic banking products in facilitating access to capital and optimizing financial management of MSMEs. The results show that the use of digital-based Islamic banking services can improve operational efficiency, expand market reach, and strengthen the financial resilience of MSMEs. This research provides strategic insights for the development of Islamic banking products in Indonesia in supporting the development of MSMEs in the digital era.